Reports on hospitals and the patient and a domestic workers' charter - Great Britain. Standing Joint Committee of Industrial Women's Organisations ; Labour Party (Great Britain). Advisory Committee on Public Health (London : Labour Party, 1931)
1931 1931 1930s 22 pages 3. NEEDS OF OUT-PATIENTS The greater use of the out-patient departments of hospitals by the public in recent years has led to many abuses of their functions and has created some of the problems of their administration, such as that of overcrowding. The main work of the out-patient departments should be for consultations and expert treatment by specialists and, when necessary, the after-care of inpatients. All other work can properly be undertaken by the general practitioners, especially the care of the chronic cases that at present are allowed to attend the out-patient departments of hospitals. A. Waiting. The great need in the out-patient departments is a system that will do away with the long hours of waiting which out-patients now have to suffer. At present they often arrive by an early train, and spend many hours in uncomfortable seats and surroundings to wait their turn. This is largely due to the belief that as they get their attendance for nothing they must suit the convenience of the hospital. But even this inhuman argument does not fit the circumstances of to-day, since charges are often made. In our view there is no reason why a time-table for patients should not be drawn up so that waiting may be reduced to a reasonable minimum for each patient. In America it is the custom to have an office attached to the hospital where appointments are made for the out-patient department. This system has been tried with great success in at least one hospital in this country. B. Accommodation. Accommodation for waiting is especially important if the period is to be a long one. Today the cheerless discomfort is often such as to reduce patients to a pitiful state of nervous exhaustion. In some cases persons with skin diseases or some other complaint of an unpleasant or infectious character are packed closely together for a long wait, and sights and sounds of an unnerving character are a bad introduction to an interview with the doctor. There should always be a rest-room, (14) 126/TG/RES/X/1036A/7